Gender differences in the accuracy of dietary assessment methods to measure energy intake in adults: protocol for a systematic review and meta-analysis. Issue 6 (1st June 2020) - McKenzie, Briar L; Coyle, Daisy H; Burrows, Tracy; Rosewarne, Emalie; Peters, Sanne A E; Carcel, Cheryl; Collins, Clare E; Norton, Robyn; Woodward, Mark; Jaacks, Lindsay M; Webster, Jacqui
Abstract : Introduction: Diet is an important modifiable risk factor for many chronic diseases. Measurement of dietary intake usually relies on self-report, subject to multiple biases. There is a need to understand gender differences in the self-report of dietary intake and the implications of any differences in targeting nutrition interventions. Literature in this area is limited and it is currently unknown whether self-report dietary assessment methods are equally accurate for women and men. The aim of this systematic review is to determine whether there are differences by gender in reporting energy intake compared with a reference measure of total energy expenditure. Methods and analysis: A comprehensive search of published original research studies will be performed in MEDLINE, Scopus, Web of Science, EMBASE, CINAHL and Cochrane library. Original research studies will be included if they were conducted in free-living/unhospitalised adults and included a measure for both women and men of (a) self-reported energy intake and (b) total energy expenditure by doubly labelled water. One author will conduct the electronic database searches, two authors will independently screen studies, conduct a quality appraisal of the included studies using standardised tools and extract data. If further information is needed, then study authors will be contacted. If appropriate, a random-effects meta-analysis will be conducted, with inverse probability weighting, to quantify differences in the mean difference in agreement between reported energy intake and measured energy expenditure between women and men, by self-report assessment method. Subgroup analyses will be conducted by participant factors, geographical factors and study quality. Ethics and dissemination: All data used will be from published primary research studies or deidentified results provided at the discretion of any study authors that we contact. We will submit our findings to a peer-reviewed scientific journal and will disseminate results through presentations at international scientific conferences. PROSPERO registration number: CRD42019131715.